2022
DOI: 10.1177/1045389x221117495
|View full text |Cite
|
Sign up to set email alerts
|

Design and modeling of a magnetorheological damper with double annular damping gap

Abstract: In this paper, a design method of magnetorheological damper with double annular damping gap is proposed. The analytical solution of the annular damping gap and the calculation model of damping force at high velocity are obtained through theoretical deduction. First of all, in view of the low magnetic field utilization rate and small dynamic range of the traditional magnetorheological damper, this paper designs a magnetorheological damper with double annular damping gap. Through the magnetic circuit simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The experimental results demonstrated that the energy consumption capacity and adjustable performance of the damper are better than those of a single-coil magnetorheological damper. Yan and Dong (2022) designed a magnetorheological damper with a double-ring damping gap to address the issues of low magnetic field utilization and small dynamic range in traditional magnetorheological dampers .meet the performance requirements of heavyduty trucks, Yang et al (2023) proposed a stepped bypass magnetorheological damper.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the energy consumption capacity and adjustable performance of the damper are better than those of a single-coil magnetorheological damper. Yan and Dong (2022) designed a magnetorheological damper with a double-ring damping gap to address the issues of low magnetic field utilization and small dynamic range in traditional magnetorheological dampers .meet the performance requirements of heavyduty trucks, Yang et al (2023) proposed a stepped bypass magnetorheological damper.…”
Section: Introductionmentioning
confidence: 99%
“…The controllable motion characteristics of the MRD should be accurately modeled to efficiently and accurately use them [14][15][16][17][18]. In the development process, MRDs have been incorporated as numerous structures [19][20][21][22], leading to great differences in the theoretical mathematical modeling. In addition MRDs have hysteretic characteristics that are difficult to describe with theoretical equations [3].…”
Section: Introductionmentioning
confidence: 99%
“…The current research on semi-active dampers focuses on smart materials, 12 for instance, magnetic fluid (MF), 13 magnetorheological fluid (MRF), 14 Since the smart materials can be adjusted according to external needs, they have a wide range of applications in damping, lubrication, etc. 15,16 Due to the large yield stress and damping force of MRF, it has been widely used in the field of damping, for instance, MRF dampers with double annular damping gap, 17 Integral MRF dampers, 18 MRF dampers for FUZZY-PID controller. 19 However, micron-scale MRF tend to aggregate and precipitate with poor stability.…”
Section: Introductionmentioning
confidence: 99%